2012
DOI: 10.3389/fphys.2012.00245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n−3 Polyunsaturated Fatty Acids on Cardiac Ion Channels

Abstract: Dietary n−3 polyunsaturated fatty acids (PUFAs) have been reported to exhibit antiarrhythmic properties, and these effects have been attributed to their capability to modulate ion channels. In the present review, we will focus on the effects of PUFAs on a cardiac sodium channel (Nav1.5) and two potassium channels involved in cardiac atrial and ventricular repolarization (Kv) (Kv1.5 and Kv11.1). n−3 PUFAs of marine (docosahexaenoic, DHA and eicosapentaenoic acid, EPA) and plant origin (alpha-linolenic acid, ALA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…Cellular, animal, and clinical studies support a hypoexcitable and antiarrhythmic effect of fish oil and PUFAs on the heart (38)(39)(40)(41)(42). One main hypothesis put forward to explain the beneficial effect is PUFA-induced inhibition of cardiac sodium and calcium channels (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular, animal, and clinical studies support a hypoexcitable and antiarrhythmic effect of fish oil and PUFAs on the heart (38)(39)(40)(41)(42). One main hypothesis put forward to explain the beneficial effect is PUFA-induced inhibition of cardiac sodium and calcium channels (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…One main hypothesis put forward to explain the beneficial effect is PUFA-induced inhibition of cardiac sodium and calcium channels (41)(42)(43)(44)(45)(46). Some studies also describe shortening of the cardiac action potential on PUFA administration (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the protective capacity of ω-3 PUFAs against cardiovascular disease has been extensively reported in plenty of animal studies [12, 13] and clinical trials [14], namely that ω-3 PUFAs can effectively reduce the incidence of cardiovascular disease and mortality [15]. It has been demonstrated that ω-3 fatty acid supplementation can modulate the cardiac ion channels involved in cardiac action potentials on the cardiomyocytes, and reduce the ω-6/ω-3 fatty acid ratio in the cardiomyocytes membrane phospholipid bilayer to exhibit antiarrhythmic properties and attenuate myocardial I/R injury [16]. In addition, ω-3 PUFAs combined with flax lignan concentrate treatments significantly reduce cardiomyocyte apoptosis and cellular oxidative stress against myocardial hypertrophy in rats [17].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In this context, n-3 PUFAs inhibit the fast sodium current, quickly activate the delayed outward potassium current and Ito, rapidly activate the delayed rectifying outward potassium current, Ltype calcium inward current, and Na + -Ca 2+ exchange current, and enhance the slowly activating delayed rectifying outward potassium current and inward rectifying potassium current. 9) These modulations of the ion channels might lead to inhibition of triggered activity 22) and shortening of the action potential. 23) Furthermore, the effects of Ito inhibition by n-3 PUFAs might restore electrical homogeneity (similar to the effects of quinidine).…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Furthermore, the n-3 PUFAs, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have antiarrhythmic effects, possibly via the modulation of cardiac ion channels. 9) Therefore, low levels of n-3 PUFAs could be potential therapeutic targets for SCD in patients with BrS.…”
mentioning
confidence: 99%